Analysis of the Rumen Microbiota of Beef Calves Supplemented During the Suckling Phase - Lourenco, Jeferson M.; Callaway, Todd R.; Kieran, Troy J.; Glenn, Travis C.; McCann, Joshua C.; Stewart, R. Lawton (Frontiers in Microbiology, 2019)
A study was conducted to examine the effects of supplementing beef calves during their suckling phase (popularly known as creep feeding) with supplements that contained or not the enzyme xylanase. Forty-two cow-calf pairs were divided into 3 groups and assigned to one of three treatments for a period of 105 days, includin: 1) No supplemental feed for calves (control; CON); 2) Corn and soybean meal-based supplement feed for calves (positive control; PCON); and 3) Same feed regimen as PCON with xylanase added to the supplement (enzyme; ENZ). After 105 days, out of the 42 calves participating in the study, 25 male calves were randomly selected (8 from CON, 9 from PCON, and 8 from ENZ) and samples of their forestomach were collected by esophageal tubing. Immediately after this procedure, all calves were weaned, commingled, and placed in a common post-weaning diet for 4 weeks. At the end of this period, ruminal fluid was once again collected from the same 25 calves. All samples were subjected to DNA extraction and 16S rRNA gene sequencing. At weaning, most of the alpha diversity indexes were greater in CON; however, no differences (P ≥ 0.23) in alpha diversity were observed in samples collected 4 weeks after weaning. Regardless of treatment, 2 phyla – Bacteroidetes and Firmicutes – comprised approximately 80% of the total bacterial abundance of samples collected on both days. At the genus level, an effect of diet (P = 0.02) was observed for Prevotella in the samples collected at weaning; however, no differences were detected in the samples collected 4 weeks after weaning. Calf average daily gain (ADG) during the 105-day creep feeding trial tended (P = 0.09) to be greater in the groups that received supplementation, with the greatest numerical value observed in ENZ. Moreover, there was a positive correlation (ρ = 0.43; P = 0.03) between ADG and abundance of Prevotella, indicating the importance of this bacterial group for ruminants. In summary, most of the significant differences found in this study were detected at weaning, and the majority of them disappeared 4 weeks after the calves were weaned and commingled.